IMPACT OF SOCIAL MEDIA MARKETING AND DESTINATION IMAGE ON TOURIST SATISFACTION THROUGH VISIT DECISION AS A MEDIATING VARIABLE - Kasih, Deta Irama; Herlambang, Toni; Sanosra, Abadi (Universitas Ibn Khaldun Bogor, 2024)
This study aims to investigate the impact of Social Media Marketing (SMM) and Destination Image on Tourist Satisfaction, with Visiting Decision serving as a mediating variable. Utilizing a Structural Equation Modeling (SEM) approach with Warp PLS 8.0 software, the research encompasses a population of both international and local tourists visiting Jember Regency. Data collection involved incidental sampling and a structured questionnaire, with a sample size of 150 respondents. The findings reveal that SMM and Destination Image significantly influence both Visiting Decision and Tourist Satisfaction. SMM directly enhances tourist satisfaction (β = 0.24, P < 0.01) and affects visiting decisions (β = 0.42, P < 0.01), while Destination Image also positively impacts tourist satisfaction (β = 0.15, P = 0.03) and visiting decisions (β = 0.43, P < 0.01). Moreover, Visiting Decision significantly mediates the relationship between SMM (β = 0.20, P < 0.01), Destination Image (β = 0.21, P < 0.01), and Tourist Satisfaction. These results underscore the need for optimized SMM strategies and a positive destination image to improve tourist satisfaction and visiting decisions in Jember Regency. The study provides valuable insights for policymakers and stakeholders to enhance tourism strategies, ensuring a satisfying and memorable tourist experience.